2018
DOI: 10.2196/preprints.10245
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving Provider Adoption With Adaptive Clinical Decision Support Surveillance: An Observational Study (Preprint)

Abstract: Background: Successful clinical decision support (CDS) tools can bring evidence-based medicine to the point-of-care to effectively improve patient outcomes. However, the impact of these tools has been limited by low provider adoption due to over-triggering, leading to alert fatigue. We have developed a tracking mechanism for monitoring trigger rate (percent of total visits for which the tool triggers) and adoption rate (percent of completed tools) of a complex CDS tool based on the Wells' Criteria for pulmonar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Although CDSS has a positive effect on health-care quality, and reduction of medication costs, rates of CDSS utilization and adoption are still low [4,5]. Prior studies explained this low adoption by the alerts' fatigue caused by CDSS [6,7,8]. Prior studies have also reported conflicting results regarding CDSS effects [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although CDSS has a positive effect on health-care quality, and reduction of medication costs, rates of CDSS utilization and adoption are still low [4,5]. Prior studies explained this low adoption by the alerts' fatigue caused by CDSS [6,7,8]. Prior studies have also reported conflicting results regarding CDSS effects [9].…”
Section: Introductionmentioning
confidence: 99%